Biodegradation of Reactive Yellow-145 azo dye using bacterial consortium: A deterministic analysis based on degradable Metabolite, phytotoxicity and genotoxicity study. (August 2022) - Singh, Asha Lata; Chaudhary, Sneha; Kumar, Sunil; Kumar, Aniruddha; Singh, Achuit; Yadav, Akhilesh
Abstract: Azo dyes are used at larger-scale as coloring agent in the textile industry. It generates a huge amount of dye containing wastewater and its toxicity threatens all kinds of life and also impacts human beings. At present, more impetus is being given to the biological treatment of dye effluent because of its azoreductase enzyme action to break down azo bond which leads to decolorization and degradation of dye. Bacterial consortium of E. asburiae and E. cloacae (1:1 ratio) was used for degradation and decolorization of Reactive Yellow-145 (RY-145) dye. The optimization of dye concentration, temperature, pH, and media has been carried out to determine the conditions required for maximum degradation and decolorization. The mixed consortium (10%) has shown 98.78% decolorization of RY-145 dye under static condition at 500 mgL −1 concentration, 35 °C and pH 7.0 at 12 h contact period. FTIR analysis showed formation of new functional groups in the treated dye, such as O–H stretch at 1361 cm −1, C–H stretch at 890 cm −1, N –H stretch at 1598 cm −1 and aromatic C–H at 671 cm −1 revealing degradation of dye. Biodegraded metabolites of RY-145 dye were identified through GC-MS analysis that includes 2-Cyclohexen-1-ol, 5-Nitroso-2, 4, 6-triaminopyrimidine, Octahydroquinoline-9-hydroxyperoxide, Tetramethyl-2-hexadecen-1-ol, 9-Octadecanoic acid, methyl ester and Hexadecanoic acid, methyl ester, respectively which have industrial applications. Cyclohexane was used in gasoline and adhesive while Octahydroquinoline-9-hydroxyperoxide and 5-Nitroso-2, 4, 6-triaminopyrimidine were used in manufacturing drugs. Tetramethyl-2-hexadecen-1-ol, 9-Octadecanoic acid, methyl ester and Hexadecanoic acid, methyl ester are antimicrobial and antioxidant. Phytotoxicity test also showed non-toxic effects of treated dye on germination of Cicer arietinum and Vigna radiata seeds. Similarly, genotoxicity study indicated less toxic effects of biodegraded dye products on Mitotic index (MI) and cell division of Allium cepa . Graphical abstract: Image 1 Highlights: Consortium of E. asburiae and E. cloacae degraded and decolorized RY-145 dye. Consortium could do it at varied pH, temperature and initial concentration. FT-IR and GC-MS analyses revealed that degraded metabolites have a commercial value. Phytotoxicity and genotoxicity study confirmed less toxicity of dye products.